The kidney transplant operation - Sheriffdeen, A.H.; Sheriff, M.H.R. (My University, 1986)
Litus Thirimanne aged 38 years in end stage of renal disease was admitted for transplantation on 4th October 1985. Several swabs were taken from nose, mouth and ears for culture. His abdomen was prepared that evening with iodine paint. No shaving was undertaken in the ward. Similar abdominal preparation was done on the, morning and evening of the 5th October. At 11.00 p.m. he was aneasthetised. A Foley catheter was introduced. 200 ml. of saline and cefuroxime 750 mg. was introduced into bladder. A right supralinguinal muscle cutting incision was made preserving his spermatic cord. On mobilization of the peritoneum it was found that due to his hypertensive disease, he had a tubular aneurismal dilation of his common iliac artery which was approximately 3 cm. in diameter. The internal iliac artery hence had become shorter than usual. The internal iliac artery was mobilized. On mobilization of the common and external iliac veins a similar dilatation was found which formed a sharp narrowing at the external/common iliac vein Junction. A local resection and end to end anastomosis of this vein was done. The donor kidney was now removed from the father, flushed with ice cold Hartman's solution and laid in the recipient's right iliac fossa bed. The renal vein was anastomosed end to side and the renal artery end to end. When the clamps were removed the kidney perfused well and there was immediate production of urine via the donor ureter. The bladder was next opened and with a submucosal tunnel, ureteroneocystostomy was done. The incision was now closed leaving a Redivac drain.